The dimeric ectodomain of the alkali-sensing insulin receptor–related receptor (ectoIRR) has a droplike shape - Shtykova, Eleonora V. (J Biol Chem, 2019)
Insulin receptor–related receptor (IRR) is a receptor tyrosine kinase of the insulin receptor family and functions as an extracellular alkali sensor that controls metabolic alkalosis in the regulation of the acid–base balance. In the present work, we sought to analyze structural features of IRR by comparing them with those of the insulin receptor, which is its closest homolog but does not respond to pH changes. Using small-angle X-ray scattering (SAXS) and atomic force microscopy (AFM), we investigated the overall conformation of the recombinant soluble IRR ectodomain (ectoIRR) at neutral and alkaline pH. In contrast to the well-known inverted U-shaped (or λ-shaped) conformation of the insulin receptor, the structural models reconstructed at different pH values revealed that the ectoIRR organization has a “droplike” shape with a shorter distance between the fibronectin domains of the disulfide-linked dimer subunits within ectoIRR. We detected no large-scale pH-dependent conformational changes of ectoIRR in both SAXS and AFM experiments, an observation that agreed well with previous biochemical and functional analyses of IRR. Our findings indicate that ectoIRR's sensing of alkaline conditions involves additional molecular mechanisms, for example engagement of receptor juxtamembrane regions or the surrounding lipid environment.